2016
DOI: 10.1016/j.neo.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Mirvetuximab Soravtansine (IMGN853), a Folate Receptor Alpha–Targeting Antibody-Drug Conjugate, Potentiates the Activity of Standard of Care Therapeutics in Ovarian Cancer Models

Abstract: Elevated folate receptor alpha (FRα) expression is characteristic of epithelial ovarian cancer (EOC), thus establishing this receptor as a candidate target for the development of novel therapeutics to treat this disease. Mirvetuximab soravtansine (IMGN853) is an antibody-drug conjugate (ADC) that targets FRα for tumor-directed delivery of the maytansinoid DM4, a potent agent that induces mitotic arrest by suppressing microtubule dynamics. Here, combinations of IMGN853 with approved therapeutics were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 57 publications
(69 reference statements)
1
51
0
1
Order By: Relevance
“…Preclinical data suggested that mirvetuximab soravtansine and PLD exert synergistic antitumor effects on ovarian cancer cells and, importantly, these effects translated to improved and durable efficacy over respective single-agent treatments alone (with good tolerability) in platinum-resistant, patient-derived xenografts [79]. Dose-escalation results from FORWARD II demonstrated that the combination was practical, with the highest dosing level evaluated being 6.0 mg/kg (AIBW) mirvetuximab soravtansine and 40 mg/kg PLD administered on day 1 of a 4-week cycle (n = 16) [82].…”
Section: Mirvetuximab Soravtansine Plus Pldmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical data suggested that mirvetuximab soravtansine and PLD exert synergistic antitumor effects on ovarian cancer cells and, importantly, these effects translated to improved and durable efficacy over respective single-agent treatments alone (with good tolerability) in platinum-resistant, patient-derived xenografts [79]. Dose-escalation results from FORWARD II demonstrated that the combination was practical, with the highest dosing level evaluated being 6.0 mg/kg (AIBW) mirvetuximab soravtansine and 40 mg/kg PLD administered on day 1 of a 4-week cycle (n = 16) [82].…”
Section: Mirvetuximab Soravtansine Plus Pldmentioning
confidence: 99%
“…(2018) 14(2) future science group A review of mirvetuximab soravtansine in the treatment of platinum-resistant ovarian cancer Drug Evaluation treatment (including carboplatin, PLD and bevacizumab) in preclinical models [79]. These observations provided a framework for an ongoing Phase Ib/II study evaluating mirvetuximab soravtansine in combination with bevacizumab, carboplatin, PLD or pembrolizumab in patients with ovarian cancer (FORWARD II, NCT02606305).…”
mentioning
confidence: 99%
“…Once the average group size tumor volume was approximately 0.159 cm 3 , the mice were randomized into treatment groups (ie, 6 to 7 per group); each group was treated with either IMGN853 (5 mg/kg), isotype control (5 mg/kg), M9346A (5 mg/kg) or PBS. Drug dosages were chosen according to previous studies conducted on xenograft models (18,32). All treatment drugs were given as retro-orbital intravenous (IV) weekly injections for two doses based on prior literature (18,32).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, mirvetuximab soravtansine exhibited robust single-agent antitumor activity in vivo (at doses well below its maximum-tolerated dose) in multiple cell line and patient-derived xenograft models of ovarian and other FRα-positive cancers [35]. Preclinical activity of this ADC in combination with standard-of-care therapeutics used in the management of ovarian cancer has also been reported [36] and those data provided the framework for an ongoing combination Phase Ib trial in patients with advanced ovarian cancer (FORWARD II). …”
mentioning
confidence: 92%